Application of the load separation criterion in J-testing of ductile polymers: A round-robin testing exercise. (July 2015) - Agnelli, S.; Baldi, F.; Blackman, B.R.K.; Castellani, L.; Frontini, P.M.; Laiarinandrasana, L.; Pegoretti, A.; Rink, M.; Salazar, A.; Visser, H.A.
Abstract: Round robin tests carried out under the direction of the Technical Committee 4 of the European Structural Integrity Society (ESIS TC4) have shown that, for determining the fracture resistance of ductile polymers at low loading rates, the multi-specimen methodology based on the construction of the material crack growth resistance curve often does not provide reliable data due to the uncertainties associated with the measurement of crack advancement (Δa). With the aim of strengthening this multi-specimen methodology, the ESIS TC4 attention has been recently focused on the analysis of a testing scheme based on the load separation criterion, which does not require the measurement of Δa. The present work gives the results of a multi-laboratory round-robin testing exercise carried out by ESIS TC4 in order to assess the degree of reproducibility of the fracture parameters obtainable with the application of this load separation criterion based testing scheme. Encouraging results have been obtained.